2012
DOI: 10.2500/ajra.2012.26.3809
|View full text |Cite
|
Sign up to set email alerts
|

The Young's Procedure for Severe Epistaxis from Hereditary Hemorrhagic Telangiectasia

Abstract: The Young's procedure is a safe and efficacious procedure with complete cessation of epistaxis in most patients with severe epistaxis and HHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…26 Epistaxis can also be managed through surgical ligation of the feeding artery as well as endovascular embolization. [34][35][36] Intranasal and intravenous bevacizumab has been shown to be effective in reducing epistaxis frequency and severity in patients with HHT and is currently a focus of studies in these patients.…”
Section: Epistaxismentioning
confidence: 99%
“…26 Epistaxis can also be managed through surgical ligation of the feeding artery as well as endovascular embolization. [34][35][36] Intranasal and intravenous bevacizumab has been shown to be effective in reducing epistaxis frequency and severity in patients with HHT and is currently a focus of studies in these patients.…”
Section: Epistaxismentioning
confidence: 99%
“…The most common clinical feature in HHT is epistaxis (nosebleeds), which often occurs on a daily basis . More than 90% of HHT patients experience spontaneous recurrent epistaxis secondary to telangiectasia of the nasal mucosa . The frequency and volume of blood lost through epistaxis have been shown recently to be sufficient to account for the iron deficiency commonly present in HHT patients .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency and volume of blood lost through epistaxis have been shown recently to be sufficient to account for the iron deficiency commonly present in HHT patients . Increased frequency and duration of epistaxis in HHT sufferers is also associated with a decreased quality of life, with debilitating nosebleeds very difficult to manage in clinical practice . HHT nosebleeds are recognized to be sporadic, often occurring in clusters, but reasons governing the specific timing of individual nosebleeds or nosebleed clusters have been addressed by relatively few studies …”
Section: Introductionmentioning
confidence: 99%
“…By preventing nasal airflow the lesions are protected and do not bleed. A retrospective review of 43 patients who underwent nasal closure over six years reported complete cessation of bleeding where complete closure was achieved (105) . Patients may experience a dry mouth as a result of this procedure and the resultant obligate mouth breathing, and occasionally oral or lingual lesions will bleed more than previously because of the increased airflow.…”
Section: Nasal Closurementioning
confidence: 99%